Implementasi Metode Prototyping pada Perancangan Aplikasi Electronic Ticket (E-Ticket) berbasis Android - Putri, Nugrahani; Agung Prabowo, Nugroho; Widyanto, R.Arri (Jurnal Komtika (Komputasi dan Informatika), 2019)
Public transportation is currently starting to experience very rapid development. This development is due to the increasing public demand for safety and comfort on the journey. Presentation of bus ticket availability information at this time is still manual, so potential users must come to the agent to find out the availability of tickets and make ticket reservations so that it is not uncommon if there are users who run out of bus tickets because the user does not get information directly. To facilitate prospective users in booking tickets and searching for bus departure information, an Android-based bus ticket booking application was built. This application was designed using MySQL, Adobe Dreamweaver and Android Studio. The system development method used in this study is the prototyping method. As for the testing method using BlackBox Testing. This method is used to find out if there are performance errors on the system. The purpose of this application is to make it easy for prospective bus users to search for buses and order tickets so they can be done anywhere and anytime without being bound by time and place.